IN HOUSE TRAINING MANAJEMEN RISIKO DENGAN DASAR ANALISIS OPPORTUNITY SOLUTION TREE DAN FISHBONE ANALYSIS DI RUMAH SAKIT UMUM MUHAMMADIYAH METRO - Fitri Yuli Mayasari; Windi Pertiwi; Maya Aprilianingsih; Retno Fajarwati; Nurreiza Rifky Pratama; Ka’bah Kiblat Perdamaian (LPPM Universitas Awal Bros, 2026)
Muhammadiyah Metro General Hospital faces significant challenges in risk management governance due to structural changes in management, gaps between formal guidelines and field practices, and fragmentation of medical and non-medical risk governance. This community service activity aims to improve human resource capacity in risk management through in-house training that integrates Opportunity Solution Tree (OST) analysis and Fishbone Diagram Analysis. The training was held on May 7, 2026, at Muhammadiyah Metro General Hospital, involving 22 participants from the board of directors, managers, and assistant managers. The training materials included basic risk management concepts, the Failure Mode and Effects Analysis (FMEA) methodology based on three Risk Priority Number (RPN) parameters, and the application of Fishbone Diagrams and Opportunity Solution Trees as thinking tools in designing mitigation programs. The evaluation results using a paired t-test showed an increase in the average score from 72.35% (pre-test) to 85.88% (post-test), with a difference of 13.53%. This activity resulted in the strengthening of proactive risk assessment guidelines, standardization of the use of three risk assessment parameters (Severity, Frequency, Detection), and the adoption of a systematic framework for designing mitigation programs. Long-term implications of this activity include transforming the risk management paradigm from reactive to proactive, establishing integrated Enterprise Risk Management, and improving patient safety and corporate governance at Muhammadiyah Metro Hospital.